Secularization, Profanation, and Knowledge of the Heart in Contemporary French Fiction - Roy Peachey (Religions)
Given the highly contested nature of the debate over secularization in modern literature, this paper examines the ways in which four contemporary French novelists address questions of human and divine absence in their fiction, focusing on Joël Egloff’s J’enquête, Gaspard-Marie Janvier’s Le dernier dimanche, Jérôme Ferrari’s Le sermon sur la chute de Rome, and Sylvie Germain’s Tobie des marais. It argues that some of the most pressing questions of our secular age—including questions of intersubjectivity and human and divine absence—are addressed in these competing narratives of secularization. It then examines Jean-Louis Chrétien’s notion of cardiognosie, or knowledge of the heart, and his argument that profanation, rather than secularization as such, is of central importance in the modern novel’s construction of meaning before concluding with a close reading of Jérôme Ferrari’s Le sermon sur la chute de Rome and a consideration of the heart in Sylvie Germain’s Tobie des marais as a first step toward establishing the means by which profanation has been faced and overcome in recent fictional texts.